Zimbabwean transnational migration, (in) visible masculinities, and the reconfiguration of gender in Shimmer Chinodya’s chairman of fools - Musanga, Terrence (Sage Publications, 2016)
This article examines the effect of the relationship between Zimbabwean transnational migration and gender on the concept of “invisible masculinities” and how the space that would have been evacuated by these “masculinities,” as a direct consequence of the migratory experience, is reorganized or reconfigured in Shimmer Chinodya’s Chairman of Fools. This space, both marital and familial, compels us to reconfigure our conceptualization of masculinities and femininities, gender relations, and gendered identities in general. However, men’s temporary or permanent return migration results in return masculinities being forced to accept the changes provoked by their absence and in the process transforming gender relations and gendered identities into more democratic spaces of interaction. The transformation of these gender relations and gendered identities also triggers changes in the marriage institution as spouses begin to see and interact with each other as partners and equals. In addition, the changes witnessed in gender relations and gendered identities result in the production of a tolerant masculinity that is adaptive, flexible, and reflexive.